Can mesopelagic mixed layers be used as feed sources for salmon aquaculture?. (October 2020) - Olsen, R.E.; Strand, E.; Melle, W.; Nørstebø, J.T.; Lall, S.P.; Ringø, E.; Tocher, D.R.; Sprague, M.
Abstract: Salmon aquaculture is in great need of good quality balanced protein and lipid sources, particularly marine omega-3 (n-3) long-chain polyunsaturated fatty acids (LC-PUFA), to sustain a further development of the industry. One possibility is to harvest mesopelagic marine layers. Therefore, the current project analysed mesopelagic hauls from three cruises (November 2015 to October 2016) collected from the inner fjord systems around Bergen and in open-waters off Tromsø and Ålesund, Norway. Jellyfish, krill, shrimps and small amounts of the mesopelagic fish, Maurolicus muelleri and Benthosema glaciale, dominated the mixed mesopelagic hauls. Lipid content ranged between 35-40% of dry matter with two samples from autumn being 21 and 13%, with the latter haul being almost exclusively krill. In contrast, M. muelleri and B. glaciale had lipid contents of around 54 and 47% respectively. Overall, lipid was a relatively good source of marine n-3 LC-PUFA, EPA and DHA, being in the range of 15–20% of fatty acids which increased in lean samples. However, many of the trawl hauls contained wax esters (7 out of 9 hauls), equivalent to 40% or more of the lipid, with B. glaciale containing almost 90% wax esters of lipid. This presents a challenge if used in salmon diets, as their utilisation is limited. Protein contents ranged between 45-50%, increasing in lean samples. The essential amino acid content was well above the requirements for Atlantic salmon ( Salmo salar ) with B. glaciale generally containing higher levels compared to M. muelleri . Leucine, lysine and valine levels were particularly high. Hauls from open-waters contained mixtures of amphipods resulting in cadmium levels exceeding the maximum allowable level in feedstuffs. Arsenic levels were high or borderline. Reducing crustacean mix in hauls appear to be the only option to reduce these levels, whereas mesopelagic fish contained low levels of all heavy metals. In summary, the mesopelagic layer contains protein and lipid sources that could supply raw materials to the salmon aquaculture industry. However, high levels of wax esters, cadmium and arsenic needs to be addressed.